Hanging out at the club: Breeding status and territoriality affect individual space use, multi‐species overlap and pathogen transmission risk at a seabird colony. (8th December 2022) - Lamb, Juliet; Tornos, Jeremy; Dedet, Romain; Gantelet, Hubert; Keck, Nicolas; Baron, Juliette; Bely, Marine; Clessin, Augustin; Flechet, Aline; Gamble, Amandine; Boulinier, Thierry
Abstract: Wildlife movement ecology often focuses on breeders, whose territorial attachments facilitate trapping and following individuals over time. This leads to incomplete understanding of movements of individuals not actively breeding due to age, breeding failure, subordinance, and other factors. These individuals are often present in breeding populations and contribute to processes such as competition and pathogen spread. Therefore, excluding them from movement ecology studies could bias or mask important spatial dynamics. Loafing areas offer an alternative to breeding sites for capturing and tracking individuals. Such sites may allow for sampling individuals regardless of breeding status, while also avoiding disturbance of sensitive breeding areas. However, little is known about the breeding status of individuals attending loafing sites, or how their movements compare to those of breeders captured at nests. We captured a seabird, the brown skua, attending either nests or loafing areas ('clubs') at a multi‐species seabird breeding site on Amsterdam Island (southern Indian Ocean). We outfitted skuas with GPS‐UHF transmitters and inferred breeding statuses of individuals captured at clubs using movement patterns of breeders captured at nests. We then compared space use and activity patterns between breeders and nonbreeders. Both breeding and nonbreeding skuas attended clubs. Nonbreeders ranged more widely, were more active, and overlapped more with other seabirds and marine mammals than did breeders. Moreover, some nonbreeders occupied fixed territories and displayed more restricted movements than those without territories. Nonbreeders became less active over the breeding season, while activity of breeders remained stable. Nonbreeding skuas were exposed to the agent of avian cholera at similar rates to breeders but were more likely to forage in breeding areas of the endangered endemic Amsterdam albatross, increasing opportunities for interspecific pathogen transmission. Our results show that inference based only on breeders fails to capture important aspects of population‐wide movement patterns. Capturing nonbreeders as well as breeders would help to improve population‐level representation of movement patterns, elucidate and predict effects of external changes and conservation interventions (e.g. rat eradication) on movement patterns and pathogen spread, and develop strategies to manage outbreaks of diseases such as highly pathogenic avian influenza. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog. Résumé: Les recherches sur l'écologie du déplacement de la faune sauvage au niveau individuel ciblent souvent des individus reproducteurs, car leur attachement territorial aux sites de reproduction facilite la capture, la recapture, et le suivi des individus à travers le temps. Au contraire, les individus qui ne reproduisent pas (à cause de leur âge, échec de reproduction, manque de dominance et autres facteurs) sont souvent exclus. Ces individus sont souvent présents aux sites de reproduction et contribuent aux processus de compétition, et de transmission des pathogènes. Par conséquence, leur exclusion des études de mouvements risque d'introduire des biais dans notre connaissance des dynamiques spatiales des populations. Les sites de repos présentent une alternative aux sites de reproduction pour la capture et suivi des individus. Ces sites présentent l'opportunité de capturer des oiseaux reproducteurs ainsi que non‐reproducteurs, tout en évitant de déranger des sites sensibles de nidification. Néanmoins, les sites de repos sont peu connus, et il est difficile de déterminer si les oiseaux qui les utilisent sont reproducteurs ou non‐reproducteurs, ou de savoir comment leurs mouvements se comparent à ceux d'oiseaux attrapés au nid. Nous avons capturé des oiseaux marins prédateurs, les labbes antarctiques, sur leurs nids ou sur des sites de repos partagés (« clubs »). Nous avons attaché des balises GPS‐UHF aux oiseaux et avons déterminé le statut reproductif des oiseaux de statut inconnu en comparant leurs mouvements à ceux de labbes capturés au nid (et donc clairement reproducteurs). Nous avons ensuite comparé l'utilization de l'espace et les niveaux d'activité entre labbes reproducteurs et non‐reproducteurs. Les labbes reproducteurs et non‐reproducteurs étaient présents aux « clubs ». Comparés aux reproducteurs, les labbes non‐reproducteurs utilisaient des surfaces plus grandes, étaient plus actifs, et exploitaient plus souvent des zones utilisées par d'autres espèces d'oiseaux et de mammifères marins. Par ailleurs, quelques labbes non‐reproducteurs occupaient des territoires fixes et présentaient des mouvements plus limités que ceux qui n'occupaient pas de territoire. Les labbes non‐reproducteurs étaient autant exposés à l'agent du choléra aviaire que les reproducteurs, mais ils se nourrissaient plus souvent dans l'habitat de l'albatros d'Amsterdam (une espèce en danger), augmentant leur probabilité de transmettre des pathogènes à cette espèce. Nos résultats montrent que les études de déplacement ne ciblant que les oiseaux reproducteurs ne représentent les déplacements de la population générale que de manière imparfaite. Capturer des oiseaux sur des sites de repos peut ainsi améliorer le taux de représentation. Le suivi des individus non‐reproducteurs, de labbes ou d'autres espèces, peut aider à prédire les effets de changements des conditions externes (comme l'éradication des rats sur l'Amsterdam ou l'apparition et transmission de la grippe aviaire) qui peuvent altérer les dynamiques éco‐épidemiologiques et les interactions entre espèces.